The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.21608/edj.2019.72578
|View full text |Cite
|
Sign up to set email alerts
|

Socket Shield and Bioactive Glass Around Anterior Maxilla Immediate Dental Implants

Abstract: Introduction: This study aimed at testing the effect of the socket shield technique on the maintenance of the labial plate of bone and the change in position of its surrounding gingival soft tissues upon the immediate placement of 3 different dental implants systems, with a bone graft material filling the defects around the implants, followed by clinical and radiographic evaluation using the cone beam computed tomography after 4 and 12 months of loading. Materials and Methods: Three groups, 6 male patients eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 70 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…Detailed analysis showed that of the included studies, 3 were randomized controlled trials,[ 18 21 30 ] 7 were retrospective studies,[ 11 15 16 17 19 22 25 ] 4 were prospective studies,[ 23 24 26 28 ] 1 was a prospective case series,[ 20 ] 1 was a prospective nonrandomized controlled study[ 27 ] and 2 were comparative studies. [ 14 29 ] A quantitative analysis of the total number of patients, the total number of implants placed with SST and complications associated with the SST is presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Detailed analysis showed that of the included studies, 3 were randomized controlled trials,[ 18 21 30 ] 7 were retrospective studies,[ 11 15 16 17 19 22 25 ] 4 were prospective studies,[ 23 24 26 28 ] 1 was a prospective case series,[ 20 ] 1 was a prospective nonrandomized controlled study[ 27 ] and 2 were comparative studies. [ 14 29 ] A quantitative analysis of the total number of patients, the total number of implants placed with SST and complications associated with the SST is presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 26 ] reported the bone loss at the neck, middle, and root of the implants as 0.27 ± 0.21 mm, 0.19 ± 0.20 mm, and 0.28 ± 0.29 mm, respectively, in 10 cases of SST. Walid and Alkhodary[ 28 ] reported no significant changes in the thicknesses of the labial bone plate and absence of vertical resorption with SST during 1 year of follow-up. In a prospective nonrandomized controlled study by Xu et al .,[ 27 ] the labial bone thickness after 1 year was found to be 2.90 ± 0.64 mm in the SST group and 2.51 ± 0.69 mm with the conventional technique.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations